2008
DOI: 10.3324/haematol.11789
|View full text |Cite
|
Sign up to set email alerts
|

Hb Foggia or  117(GH5)Phe -> Ser : a new  2 globin allele affecting the  Hb-AHSP interaction

Abstract: LETTERS TO THE EDITORHb Foggia or ␣ ␣117(GH5)Phe→ →Ser: a new ␣ ␣2 globin allele affecting the ␣ ␣Hb-AHSP interaction We report a novel ␣ ␣2-globin gene allele with the mutation cod 117 TTC>TCC or ␣ ␣117(GH5)Phe>Ser detected in three carriers with ␣ ␣-thalassemia phenotype. The mutated mRNA was present in the reticulocytes in the same amount as the normal one, but no chain or hemoglobin variant were detected. Most likely the amino acid substitution impairs the interaction of the ␣ ␣-chain variant with the AHSP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0
4

Year Published

2009
2009
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 9 publications
1
18
0
4
Order By: Relevance
“…5). Thus, these results are ambiguous, and it is unclear which disrupted interactions, AHSP:a H -chain or a 1 b 1 , give rise to the observed phenotypes (68,103). H subunits, but is not part of the interface with AHSP.…”
Section: Clinical Relevance Of Ahsp Functionmentioning
confidence: 86%
See 2 more Smart Citations
“…5). Thus, these results are ambiguous, and it is unclear which disrupted interactions, AHSP:a H -chain or a 1 b 1 , give rise to the observed phenotypes (68,103). H subunits, but is not part of the interface with AHSP.…”
Section: Clinical Relevance Of Ahsp Functionmentioning
confidence: 86%
“…Marden and co-workers have suggested that AHSP-a H -chain interactions are impeded by a proline to serine mutation at position 119 of a H chains (P119S, Hb Groene Hart), which results in an a thalassemia phenotype (102). Another novel a H chain mutation (F117S, Hb Foggia) also results in a phenotype typical of a thalassemia (68). This mutation is predicted to disrupt favorable interactions with AHSP (34,68).…”
Section: Clinical Relevance Of Ahsp Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…8,12,[25][26][27][28][29][30][31][32][33][34][35] We used the Globin Gene Server, published case reports, and crystallographic studies to identify naturally occurring ␣ globin gene mutations that alter amino acids at AHSP contact sites ( Figure 1A). 8 Some of these mutations occur at the ␣ 1 ␤ 1 interface and may also affect ␤ globin binding (Table 1; Figure 1) 8 (and www.rcsb.org).…”
Section: Resultsmentioning
confidence: 99%
“…Some ␣ globin variants contain amino acid substitutions at the AHSP-binding interface, which has been mapped by structural studies (see Globin Gene Server, http:// globin.cse.psu.edu). 8,9 Several reports describe clinically significant ␣ globin mutations that inhibit ␣ globin-AHSP interactions, including antiterminator mutations Hb Pakse and Hb Constant Springs 10,11 and missense mutations F117S (Hb Foggia) 12 and P119S (Hb Groene-Hart). 13 These studies suggest new mechanisms for hemoglobinopathies by identifying ␣ globin variants that may not be stabilized by AHSP in vivo.…”
Section: Introductionmentioning
confidence: 99%